Structure of the chorioretinal complex in the rabbit eye after vitrectomy. Report 3. Vitreous cavity irrigation with 36°С solution (Ukrainian Journal of Ophthalmology, 2025)
Background: Currently, there are no clear recommendations on temperature modes regarding safety for ocular fundus structures during vitrectomy. Our rabbit study has previously found that formation of numerous vacuoles in retinal layers represents the most apparent retinal changes after vitrectomy with prolonged irrigation with low-temperature (22°С or 5°С) fluids.Purpose: To investigate the structure of the rabbit retina and choroid after vitrectomy with prolonged irrigation with 36°С fluid.Materials and Methods: Twelve rabbits (24 eyes) were included in this study and divided into the experimental group (10 animals, 20 eyes) and the control group (2 intact animals, 4 eyes). The former group had vitrectomy with 30-minute or 60-minute irrigation with 36°С Balanced Ringer’s lactate. Vitrectomy was performed using the Alcon Accurus 400VS vitrectomy system (Alcon Laboratories). Histological studies of the choreoretinal complex (the retina and choroid) were performed at days 1 and 7 after surgery.Results: At baseline, mean rectal temperature was 38.3 ± 0.3 °С. Mean midvitreous temperature decreased from 37.4 ± 0.2°С at baseline to 36.4±0.1°С (i.e., by 1 °С) (p < 0.0002). Histological examination found no apparent vacuolization of retinal structures at the microscopic slides obtained after prolonged surgery performed under conditions of mild hypothermia compared to eyes operated under conditions of deep hypothermia with 22°С and especially 5°С fluids.Conclusion: In rabbits, the use of 36°С irrigation fluids during vitrectomy resulted in a decrease in vitreal cavity temperature to the level of mild hypothermia, with no structural changes in the chorioretinal complex within 7 postoperative days after prolonged irrigation of the vitreous cavity. A reasonable assumption can be made that, after vitrectomy with prolonged irrigation of the vitreous cavity (with the 22°С or 5°С solutions) under conditions of deep hypothermia, apparent vacuolization developed mostly due to the low-temperature effect of irrigating fluid. There is need for further research aimed at identification of the safest modes for use of local ocular hypothermia during vitrectomy and investigation of optimum temperature conditions in the postoperative period.
Keywords: vitrectomy; intraocular temperature; rabbit eye; choreoretinal complex